CRISPR/Cas9-mediated simultaneous targeting of GmP34 and its homologs produces T-DNA-free soybean mutants with reduced allergenic potential - Baek, Dongwon; Jin, Byung Jun; Park, Mi Suk; Cha, Ye Jin; Han, Tae Hee; Jang, Ye Na; Kim, Su Bin; Shim, Sang In; Chung, Jong-Il; Chun, Hyun Jin; Kim, Min Chul (Frontiers in Plant Science, 2025)
Soybean (Glycine max L.) P34 (GmP34) is a prominent allergenic seed protein belonging to the papain-like cysteine protease family. To mitigate its allergenic potential, we implemented a CRISPR/Cas9-based genome editing strategy targeting GmP34 along with its two highly similar homologs, GmP34h1 and GmP34h2, in the soybean cultivar Williams 82. Phylogenetic analysis and domain characterization identified GmP34h1 and GmP34h2 as the closest homologs to GmP34, with conserved allergenic peptide motifs. Gene expression profiling revealed similar expression patterns of all three genes during seed maturation, indicating potential functional redundancy. Two multiplex CRISPR/Cas9 constructs were designed to simultaneously target GmP34/GmP34h1 and GmP34/GmP34h1/GmP34h2 genes, respectively. Transgenic genome editing plants were generated via Agrobacterium-mediated transformation, and targeted mutagenesis was confirmed by genomic PCR and deep sequencing. Loss of GmP34 protein in edited lines was further validated through western blot analysis. Using this strategy, we successfully generated GmP34 single, GmP34/GmP34h1 double, and GmP34/GmP34h1/GmP34h2 triple mutants. This study highlights the utility of multiplex genome editing in silencing soybean allergenic gene and its homologs. Ongoing analyses of allergenicity in these edited lines aim to provide a genetic foundation for the development of hypoallergenic soybean cultivars through precise genome engineering.